The Utilization of Artificial Intelligence (AI) Translators to Improve Writing in EFL Classroom - Lazuwardiyyah, Fairuz; Setiawan, Slamet; Widyastuti, Widyastuti (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
In recent years, there has been a rapid development in Artificial Intelligence (AI), including AI translators. AI translator tools are utilized in education, especially in language learning. The current study aims to investigate the utilization of AI translators to improve the quality of students' writing in an EFL classroom. This research is a quantitative study using a questionnaire to collect data from 40 EFL students in one of the state universities in Surabaya. The data obtained were analyzed using descriptive statistics and independent-samples t-test. The results show that most students perceive positive attitudes, such as that AI translators is easy to use, can improve their writing and translation quality, and many others. However, they agreed with the negative statements, such as that machine translation is considered cheating, the issue of dependence, etc. This study also revealed no significant differences in writing quality between the students who have positive and negative attitudes towards the utilization of AI translators.